1982
DOI: 10.1111/j.1365-2125.1982.tb01947.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of plasma catecholamines to blood pressure in hypertensive patients during beta‐adrenoceptor blockade with and without intrinsic sympathomimetic activity.

Abstract: 1 This study was designed to follow changes in plasma catecholamine concentrations during ,B-adrenoceptor blockade using doses of antagonists which decreased the mean arterial pressure (MAP) by about 15 mm Hg. Noradrenaline, adrenaline and dopamine were radioenzymatically determined in 34 patients with moderate essential hypertension during an 8 week course of treatment with either pindolol (with intrinsic sympathomimetic activity, ISA) or propranolol (without ISA). Plasma catecholamines were determined before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1982
1982
1992
1992

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The levels of noradrenaline reached following exercise in the pre-treatment period were similar to those reported by us during placebo treatment. In the same study (Kirsten et al, 1982) comparison with pre-treatment values showed that postexercise noradrenaline was lower following 8 weeks treatment with pindolol. At this time, noradrenaline concentration was significantly lower during pindolol than during propranolol treatment, analogous to the findings reported here between pindolol and metoprolol after 3 weeks treatment.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…The levels of noradrenaline reached following exercise in the pre-treatment period were similar to those reported by us during placebo treatment. In the same study (Kirsten et al, 1982) comparison with pre-treatment values showed that postexercise noradrenaline was lower following 8 weeks treatment with pindolol. At this time, noradrenaline concentration was significantly lower during pindolol than during propranolol treatment, analogous to the findings reported here between pindolol and metoprolol after 3 weeks treatment.…”
Section: Discussionmentioning
confidence: 76%
“…The difficulties introduced by inadequate controls were also demonstrated in a recent study (Kirsten et al, 1982) where plasma noradrenaline following bicycle exercise was found to be lower after 4 weeks propranolol treatment, compared with pre-treatment levels. The levels of noradrenaline reached following exercise in the pre-treatment period were similar to those reported by us during placebo treatment.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations